Designed synthesis of SnO2–C hollow microspheres as an anode material for lithium-ion batteries. Issue 81 (28th September 2017) - Hu, Lin-Lin; Yang, Li-Ping; Zhang, Dong; Tao, Xian-Sen; Zeng, Chen; Cao, An-Min; Wan, Li-Jun
Abstract : We report a simple and facile synthetic protocol to prepare an SnO2 –C hollow composite, which shows improved battery performance when used as an anode material in lithium ion batteries. Abstract : We report a simple and facile synthetic protocol to prepare an SnO2 –C hollow composite, which shows improved battery performance when used as an anode material in lithium ion batteries.